High Proton-Conductive and Temperature-Tolerant PVC-P4VP Membranes towards Medium-Temperature Water Electrolysis - Yichen Yin; Yiming Ying; Guojuan Liu; Huiling Chen; Jingrui Fan; Zhi Li; Chuhao Wang; Zhuangyan Guo; Gaofeng Zeng (Membranes, 2022)
Water electrolysis (WE) is a highly promising approach to producing clean hydrogen. Medium-temperature WE (100–350 °C) can improve the energy efficiency and utilize the low-grade water vapor. Therefore, a high-temperature proton-conductive membrane is desirable to realize the medium-temperature WE. Here, we present a polyvinyl chloride (PVC)-poly(4vinylpyridine) (P4VP) hybrid membrane by a simple cross-linking of PVC and P4VP. The pyridine groups of P4VP promote the loading rate of phosphoric acid, which delivers the proton conductivity of the PVC-P4VP membrane. The optimized PVC-P4VP membrane with a 1:2 content ratio offers the maximum proton conductivity of 4.3 × 10−2 S cm−1 at 180 °C and a reliable conductivity stability in 200 h at 160 °C. The PVC-P4VP membrane electrode is covered by an IrO2 anode, and a Pt/C cathode delivers not only the high water electrolytic reactivity at 100–180 °C but also the stable WE stability at 180 °C.